2013
DOI: 10.1103/physreva.87.043414
|View full text |Cite
|
Sign up to set email alerts
|

Efficient site-specific low-energy electron production via interatomic Coulombic decay following resonant Auger decay in argon dimers

Abstract: We identified interatomic Coulombic decay (ICD) channels in argon dimers after spectator-type resonant Auger decay 2p −1 3d → 3p −2 3d,4d in one of the atoms, using momentum-resolved electron-ion-ion coincidence. The results illustrate that the resonant core excitation is a very efficient way of producing slow electrons at a specific site, which may cause localized radiation damage. We find also that ICD rate for 3p −2 4d is significantly lower than that for 3p −2 3d.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…Intriguingly it has been shown theoretically and verified experimentally that ICD is not an isolated phenomenon, but might be part of complex cascade relaxation mechanisms, occurring for instance following an Auger decay process67891011121314. To understand relaxation mechanisms, it is necessary to be aware of all possible channels and determine their significance, and in the present work, we investigated this subject.…”
mentioning
confidence: 92%
“…Intriguingly it has been shown theoretically and verified experimentally that ICD is not an isolated phenomenon, but might be part of complex cascade relaxation mechanisms, occurring for instance following an Auger decay process67891011121314. To understand relaxation mechanisms, it is necessary to be aware of all possible channels and determine their significance, and in the present work, we investigated this subject.…”
mentioning
confidence: 92%
“…14 Its detailed experimental studies in Ar 2 , ArKr, ArXe, and ArNe demonstrated the functioning of the control mechanism. [14][15][16] In these experiments, the cascade was initiated by resonant photon excitation of a 2p core electron of Ar to the 4s or the nd, n = 3, 4, 5, virtual orbital. Resulting ICD electron spectra indeed show marked dependence on the parent core excitation.…”
Section: Introductionmentioning
confidence: 99%
“…These involve the observation of ICD in rare gas dimers [5], rare gas clusters [6], surfaces [7], and small water droplets [8,9]. ICD followed by resonant Auger decay has been identified in Ar dimers using momentum resolved electron-ion-ion coincidence spectroscopy [10,11]. Ultrafast ICDs of a dicationic monomer in a cluster to produce a cluster tricataion [12] Of particular interest is the resonant ICD (RICD) where the precursor excitation to form an inner-shell vacancy is accomplished by promoting an inner electron to an excited state by an external stimulant, generally electromagnetic radiation [17,18] or, more recently, chargeparticle impact [21].…”
mentioning
confidence: 99%
“…These involve the observation of ICD in rare gas dimers [5], rare gas clusters [6], surfaces [7], and small water droplets [8,9]. ICD followed by resonant Auger decay has been identified in Ar dimers using momentum resolved electron-ion-ion coincidence spectroscopy [10,11]. Ultrafast ICDs of a dicationic monomer in a cluster to produce a cluster tricataion [12] or multiply excited homoatomic cluster [13] were predicted.…”
mentioning
confidence: 99%